2016
DOI: 10.1155/2016/9509810
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial for the Effectiveness of Aromatherapy in Decreasing Salivary Gland Damage following Radioactive Iodine Therapy for Differentiated Thyroid Cancer

Abstract: Objective. The aim of this study was to investigate effects of aromatherapy in decreasing salivary gland damage for patients undergoing radioactive iodine (RAI) therapy with differentiated thyroid cancer (DTC). Materials and Methods. The subjects were 71 patients with DTC. They were divided into aromatherapy group (group A, n = 35) and a control group (group B, n = 36). We blended 1.0 mL of lemon and 0.5 mL of ginger essential oils. The patients in the inhalation aromatherapy group inhaled this blend oil and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…A randomized controlled trial suggested that aromatherapy (1 mL of lemon and 0.5 mL of ginger essential oil) has efficacy in preventing treatment-related salivary gland disorder [ 233 ]. Interestingly, a pilot study’s outcomes have shown that administering 2 g of ginger daily in patients with high risk for colorectal cancer may improve cell-cycle biomarkers in the normal-appearing colonic mucosa [ 234 ].…”
Section: Herbal Infusions In Human Clinical Trialsmentioning
confidence: 99%
“…A randomized controlled trial suggested that aromatherapy (1 mL of lemon and 0.5 mL of ginger essential oil) has efficacy in preventing treatment-related salivary gland disorder [ 233 ]. Interestingly, a pilot study’s outcomes have shown that administering 2 g of ginger daily in patients with high risk for colorectal cancer may improve cell-cycle biomarkers in the normal-appearing colonic mucosa [ 234 ].…”
Section: Herbal Infusions In Human Clinical Trialsmentioning
confidence: 99%
“…Ginger and metoclopramide treatment are efficient to treat nausea and vomiting (Sontakke, Thawani, & Naik, 2003). Arogya-wardhani used to rescue abnormal liver functions (Antarkar, 1980) 4 Nonmelanoma Skin Cancer 45 Erythema, dermatitis, and atrophy Turmeric and sandalwood containing cream can treat dermatitis (Palatty et al, 2014) 5 Thyroid Cancer 60 Swelling or pain of salivary gland, headache, vertigo, insomnia, vocal cord paralysis, fatigue, general malaise, foreign body sensation, body numbness, and urinary tract infection Inhalation of blended 1 ml lemon and 0.5 mL of ginger essential oils showed significant improvement in salivary gland secretion (Nakayama, Okizaki, & Takahashi, 2016) 6 Colorectal Cancer 40-74 Nausea, bowel incontinence or stool leakage, fatigue, tiredness, rectal irritation, skin irritation, bladder irritation along with burning sensation or pain while urinating, diarrhea, blood in stool, vaginal irritation in women, and erection issues in men are seen abnormal chromosome with two centromere or translocated chromosomes, is an estimated risk of radiation dosage done by scoring chromosomal aberrations (Abe et al, 2016). In dicentric chromosomes, although the cells are unstable and cannot be passed through repeated mitotic division, the translocated chromosomes are stable.…”
Section: Genetic Mutations Occurring After Radiation Therapy In Cancementioning
confidence: 99%
“…Apitherapy using honey products is reportedly useful for preventing salivary gland disorders. Massage of the salivary glands and aroma therapy are also reported to relieve symptoms [18].…”
Section: Acute Salivary Gland Disordersmentioning
confidence: 99%